Growth of nitrite‐oxidizing Nitrospira and ammonia‐oxidizing Nitrosomonas in marine recirculating trickling biofilter reactors. (7th June 2022) - Oshiki, Mamoru; Netsu, Hirotoshi; Kuroda, Kyohei; Narihiro, Takashi; Fujii, Naoki; Kindaichi, Tomonori; Suzuki, Yoshiyuki; Watari, Takahiro; Hatamoto, Masashi; Yamaguchi, Takashi; Araki, Nobuo; Okabe, Satoshi
Summary: Aerobic ammonia and nitrite oxidation reactions are fundamental biogeochemical reactions contributing to the global nitrogen cycle. Although aerobic nitrite oxidation yields 4.8‐folds less Gibbs free energy ( ∆G r ) than aerobic ammonia oxidation in the NH4 + ‐feeding marine recirculating trickling biofilter reactors operated in the present study, nitrite‐oxidizing and not ammonia‐oxidizing Nitrospira (sublineage IV) outnumbered ammonia‐oxidizing Nitrosomona s (relative abundance; 53.8% and 7.59% respectively). CO2 assimilation efficiencies during ammonia or nitrite oxidation were 0.077 μmol‐ 14 CO2 /μmol‐NH3 and 0.053–0.054 μmol‐ 14 CO2 /μmol‐NO2 − respectively, and the difference between ammonia and nitrite oxidation was much smaller than the difference of ∆G r . Free‐energy efficiency of nitrite oxidation was higher than ammonia oxidation (31%–32% and 13% respectively), and high CO2 assimilation and free‐energy efficiencies were a determinant for the dominance of Nitrospira over Nitrosomonas . Washout of Nitrospira and Nitrosomonas from the trickling biofilter reactors was also examined by quantitative PCR assay. Normalized copy numbers of Nitrosomonas amoA were 1.5‐ to 1.7‐folds greater than Nitrospira nxrB and 16S rRNA gene in the reactor effluents. Nitrosomonas was more susceptible for washout than Nitrospira in the trickling biofilter reactors, which was another determinant for the dominance of Nitrospira in the trickling biofilter reactors.